TECNOLOGIA SOCIAL INDUTORA DE BOAS PRÁTICAS NO CICLO GRAVÍDICO-PUERPERAL DE MULHERES INDÍGENAS - Boer, Lubiane (2023)
Maternal and child health is considered a global priority and one of the essential public health services for achieving the Sustainable Development Goals (SDGs), which sets the goal of ensuring maternal mortality rates below 70 per 100,000 live births by 2030. This topic is also included in the Ministry of Health’s Research Priorities Agenda: Goal 14 - Maternal and Child Health. The aim was to develop, based on the Agenda of Priorities and demand previously identified by the main researcher of this study, who also holds the position of Secretary of Health in her municipality and who has 31 Indigenous Villages under supervision, the need to identify knowledge and specific practices of this culture, in order to enhance initiatives, add knowledge and discuss strategies that contribute to achieving the SDGs. The objective was: a) to identify the knowledge related to the pregnancy-puerperal cycle of Indigenous women, from the perspective of leaders in Indigenous health services; b) to identify unique experiences and practices in the pregnancy-puerperal cycle of Indigenous women; and c) to describe the strategies designed and implemented, collaboratively, in the inductive path of good practices in the pregnancy-puerperal cycle of indigenous women. The methodological path was conducted through action research, carried out throughout the year 2023, initially, based on field research with ten leaders who work in the context of Indigenous health and with 27 Indigenous pregnant women from Aldeias do Mato Grosso, Brazil, to identify unique experiences and practices of the pregnancy-puerperal cycle and, subsequently, through the implementation of strategic actions. The recommendations of Resolutions No. 466/2012 and Operational Norm No. 001 of 2013 of the National Health Council CNS were followed. The research project was approved by the National Ethics and Research Commission under opinion: 6.042.588, CAAE: 65547822.0.0000.5306. The results of this study highlighted the importance of the professional/user bond, the relevance of community health workers, who occupy a mediating and guiding role in culturally relevant aspects for indigenous women and signaled practices that can be encouraged in the Indigenous context, without mischaracterizing the peculiarities cultural and ethnic. Indigenous pregnant women, in turn, suggest inviolable practices and beliefs, which must be welcomed, respected and enhanced by Indigenous health teams. The strategies outlined and implemented in the context of Indigenous women are associated with the promotion of local policies that strengthen the nutrition of Indigenous pregnant women, considering that, for the most part, they reported weakness; qualification of Indigenous Health Workers, through a specific course; presence of more medical professionals to support health care for pregnant women as well as the entire population in their illness; and more effective approach with Indigenous pregnant and postpartum women, in order to listen to them and embrace their unique needs. Final considerations: The experiences in the pregnancy-puerperal cycle of Indigenous women are unique and inviolable. They are motivated by beliefs and practices that transcend scientific knowledge, certainties and the linearity of assistance, normally established as a hegemonic order in other cultures. To this end, specific strategies associated with strengthening the bond and mediation of nearby health workers are required, in addition to strengthening the role of Indigenous women, without violating customs, beliefs and practices specific to Indigenous culture. Product and its applicability: This is a social technology, mediated by action research, which attempted to investigate unique practical knowledge among local leaders and Indigenous pregnant women, as well as discuss and implement prospective strategies that aim to enhance sociocultural specificities in the pregnancy-puerperal cycle of Indigenous women, broaden perspectives and strengthen intercultural dialogue and, in this way, contribute to achieving the Sustainable Development Goals.